Outcomes indicators and processes in transitional care in adolescents with haemophilia: A Delphi survey of Canadian haemophilia care providers. Issue 2 (28th February 2019) - Sun, Haowei (Linda); Breakey, Vicky R.; Straatman, Lynn; Wu, John K.; Jackson, Shannon
Abstract : Introduction: It is unclear which outcome indicators should be used to measure the success of haemophilia transition programs, and what are key elements of a haemophilia transition program to ensure success. Aim: To establish by expert consensus a list of important and feasible outcome indicators of successful haemophilia transition, and a list of key elements of transition planning. Methods: A modified two‐stage Delphi survey was developed and disseminated among a panel of Canadian interdisciplinary haemophilia care providers. Participants were asked to rate the importance and feasibility of outcome indicators of effective haemophilia transition and elements of haemophilia transition program. In the second round, participants were asked to choose the top five outcomes suitable for inclusion in a core outcome set of transition effectiveness, and the top five elements that are important and feasible for implementation within the next 5 years. Results: In total, 34/73 (47%) of participants completed the first round and 33 completed the second round, representing a variety of disciplines. Top outcome indicators recommended for a core outcome set include measurement of adherence, change in bleeding rate, self‐efficacy skills, haemophilia knowledge, patient and caregiver satisfaction, time gap between last paediatric and first adult clinic, and number of emergency room or hospital admissions. Fourteen elements of transition achieved consensus in importance ratings, while eight were felt to be feasible for implementation within next 5 years. Conclusions: Results will contribute towards the development of a haemophilia transition outcome instrument and provide guidance for future studies of the effectiveness of transition programs.